Freedom walkers : the story of the Montgomery bus boycott - Freedman, Russell (New York : Holiday House, 2006)
Gr 4-6Freedman begins this outstanding history by reminding his audience that the injustices of racial segregation did not happen that long ago in the United States. Throughout the book, he gives accounts of how much coordination and sacrifice went into conducting the Montgomery Bus Boycottfar more than students are likely to imagine from the usual popular and oversimplified versions offered in textbooks and on television. There is a refreshing emphasis on depictions of regular people and forgotten local crusaders working together to make the boycott possible and triumphant, from inspiring descriptions of drivers getting up at dawn to take others to work to accounts of well-known civil-rights lawyers working to find the right plaintiff to challenge unjust laws. Freedman's prose style pulls readers into the narrative, integrating the actual recorded words and deeds of the people to tell the story. The high-quality, black-and-white photographs range from everyday scenes of African-American boycotters meeting, waiting for carpools, and protesting to representations of more famous figures, such as Rosa Parks, Martin Luther King, Jr., etc. Extensive chapter notes, an annotated selected bibliography, and a thorough index round out the exemplary presentation. Pair this volume with Ann Bausum's Freedom Riders (National Geographic) and Nikki Giovanni's Rosa (Holt, both 2005) for a powerful introduction to the Civil Rights Movement.Michael Santangelo
Includes bibliographical references and index.
KK 09/01/06, HB 09/06
0812
Keywords: African Americans -- Civil rights -- Alabama -- Montgomery -- History -- 20th century -- Juvenile literature; African Americans -- Alabama -- Montgomery -- Biography -- Juvenile literature; Civil rights workers -- Alabama -- Montgomery -- Biography -- Juvenile literature; Segregation in transportation -- Alabama -- Montgomery -- History -- 20th century -- Juvenile literature; Montgomery (Ala.) -- Race relations -- Juvenile literature; Montgomery (Ala.) -- Biography -- Juvenile literature; Biographies